2016
DOI: 10.3390/v8080229
|View full text |Cite
|
Sign up to set email alerts
|

Role of Envelopment in the HEV Life Cycle

Abstract: Hepatitis E virus (HEV), an enterically transmitted hepatotropic virus, was thought to be non-enveloped for decades. However, recent studies have revealed that the virus circulating in the patient’s blood is completely cloaked in host membranes and resistant to neutralizing antibodies. The discovery of this novel enveloped form of HEV has raised a series of questions about the fundamental biology of HEV and the way this virus, which has been understudied in the past, interacts with its host. Here, we review re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 52 publications
1
64
0
1
Order By: Relevance
“…Consistent with this, MAVS abundance is not altered in cells transfected with replication-competent HEV RNAs (Fig. 4B, bottom), although the response to RIG-I and MDA5 agonists is reduced in such cells (Nan et al 2014b;Yin et al 2016). The underlying mechanism is uncertain, but overexpression of the papain-like cysteine protease (PCP) domain of the HEV open reading frame (ORF)1 protein has been shown to result in deubiquitination of RIG-I and TBK1, thereby blocking RIG-I signaling (Nan et al 2014b).…”
Section: Innate Immunity To Enteric Hepatitis Virusessupporting
confidence: 75%
“…Consistent with this, MAVS abundance is not altered in cells transfected with replication-competent HEV RNAs (Fig. 4B, bottom), although the response to RIG-I and MDA5 agonists is reduced in such cells (Nan et al 2014b;Yin et al 2016). The underlying mechanism is uncertain, but overexpression of the papain-like cysteine protease (PCP) domain of the HEV open reading frame (ORF)1 protein has been shown to result in deubiquitination of RIG-I and TBK1, thereby blocking RIG-I signaling (Nan et al 2014b).…”
Section: Innate Immunity To Enteric Hepatitis Virusessupporting
confidence: 75%
“…HAV and presumably other nonenveloped viruses, such as HEV, hijack intracellular membranes to shield from neutralizing antibody epitopes contained in the viral capsid. Quasienvelopment is also thought to promote HAV spread within the liver but is mechanistically incompletely understood (39). For HAV, it was demonstrated that the biogenesis of the membranes surrounding virions is dependent on host proteins associated with the ESCRT pathway, specifically VPS4B and ALIX (38).…”
Section: Discussionmentioning
confidence: 99%
“…ORF1 is a polyprotein required for HEV RNA replication. ORF2 is the capsid protein, while ORF3 is a small protein involved in HEV egress (14). HEV has a unique dual life cycle: it is shed into the feces as naked virions, but circulates in the blood as "quasi-enveloped" particles (eHEV) (15).…”
mentioning
confidence: 99%